ANALISIS TENTANG PERSEPSI MAHASISWA UNIVERSITAS RIAU TERHADAP PERANAN OMBUDSMAN PERWAKILAN PROVINSI RIAU - Solihin '; Sri Erlinda; Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study is conducted base on the immaximum of public services by Riau Province apparatus. With the existence of Ombudsman representation in Riau province for quite long, show the services are given by the ombudsman are not quite well. Based on the reason of the Ombudsman establishment, as an extention for curing the public services in Indonesia specifically in Riau province. Based on this, the researchers is interested in conducting a study entitled “An analysis of Riau University student’s perception to Ombudsman representation in Riau province”. The question of this study is how the perception of Riau University student to Ombudsman representation in Riau province. The aim of this study is to know how far the roles of Ombudsman representation in Riau in doing they duties, functions and authority. The samples of this study are 180 respondents taken random that consist of 20 respondents for each facullty and using Purposive Sampling . The instruments of collecting data using quissionarre and interview. There are 32 questions which classified 10 questions to tOmbudsman duties, 1 question to Ombudsman function, and about 21 questions to Ombudsman authority. Based on data analysis , the perception of students to Ombudsman duties is very good and reach about 43.28%, in other hand the students perception about Ombudsman function considered not really good and reach around 28.33%. While to Ombudsman authority is in level very good with percentage around 49.29%. From these 3 indicators roles of Ombudsman, about 40.03% students answered “ always” reach 33.34%-66.67%. It can be concluded that the Ombudsman of Repulic of Indonesia for Riau chapter is not really well in doing they duties as an inspector institution for public services.Keywords : Students, the role of Ombudsman.